2007
DOI: 10.1088/0143-0807/28/5/009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of K shell photoelectric cross sections at a K edge—a laboratory experiment

Abstract: We describe in this paper a new method for measuring the K shell photoelectric cross sections of high-Z elemental targets at a K absorption edge. In this method the external bremsstrahlung (EB) photons produced in the Ni target foil by beta particles from a weak 90Sr-90Y beta source are passed through an elemental target and the spectrum of transmitted EB photons is measured with a HPGe detector coupled to a 2K ORTEC multichannel analyser spectrometer. The measured spectrum shows a sharp decrease in transmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…9 With help of field cooling it is possible to arrest the high temperature austenite phase below the martensitic transition temperature. 10,11 It is also observed that one can get large field induced irreversibility in the magnetization loops when measured near to the martensitic transition temperature. 12,13 In contrast to the other systems showing magnetic-glass behavior, the field induced structural change in the Heusler alloys plays a major role in inducing the irreversibilities that become stronger on approaching the martensitic transition upon increasing the temperature.…”
Section: Introductionmentioning
confidence: 95%
“…9 With help of field cooling it is possible to arrest the high temperature austenite phase below the martensitic transition temperature. 10,11 It is also observed that one can get large field induced irreversibility in the magnetization loops when measured near to the martensitic transition temperature. 12,13 In contrast to the other systems showing magnetic-glass behavior, the field induced structural change in the Heusler alloys plays a major role in inducing the irreversibilities that become stronger on approaching the martensitic transition upon increasing the temperature.…”
Section: Introductionmentioning
confidence: 95%
“…Shape memory alloys of the type Ni2Mn1+xZ1x (Z = In, Sn, or Sb) have been studied for their many novel properties like giant reverse magneto‐caloric effect , large magnetic field induced strains , magnetic superelasticity , and complex magnetic order . The origin of these effects lie in the coupling between structural and magnetic degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the experimental data sample is summarized in Tables II-III. The photoionization cross sections reported in the literature as experimentally measured often derive from measurements of total photon attenuation, from which theoretically calculated contributions from photon scattering were subtracted. These semi-empirical values are not appropriate to an epistemologically correct validation process, which requires the comparison [26], [165], [167], [169], [173], [175], [ [26], [124], [155], [165], [167]- [169], [173], [175], [176], [ [176], [178], [179], [181] of simulation models with truly experimental data. An evaluation of the possible systematic effects induced by using semiempirical data [182] - [245] as a reference for testing cross section calculations is reported in Section VII-A; it concerns a sample of approximately 1500 total cross sections, spanning energies between approximately 50 eV and 6 MeV.…”
Section: B Experimental Datamentioning
confidence: 99%